ANALISIS SISTEM ANTRIAN DAN OPTIMALISASI LAYANAN PUBLIK DI KANTOR PELAYANAN PAJAK PRATAMA PURWOKERTO - Idah, Yusyida Munsa; Suhartono, Didit (Performance, 2016)
The purpose of this study was to analyze the queuing system to provide optimum service to the community in Kantor Pelayananan Pajak Pratama Purwokerto. Data collection techniques to collect raw data obtained from direct observations of variables queuing system on the service tax at Kantor Pelayanan Pajak Pratama Purwokerto by measuring the speed of arrival of the taxpayer as well as the long service he received at each service. The variables used in this study is the dependent variable (dependent variable) is the queue, and the independent variable (independent variable) is the arrival rate taxpayer (λ), service level (μ), the optimal amount of services.The first step is to book study method is to collect, observe, analyze relevant theories. The second step is making direct observation by measuring the speed of arrival and departure of the taxpayer as well as the long pelayananan received at each service . The third step analyzing the arrival of the taxpayer in each service processed with frequency intervals of 10 minutes to find the number of arrivals and keberangktan the unity of time ( λ ) After doing the research results that the average waiting time taxpayer in the system and in the queue already meet specified target is 5 to 10 minutes .